Long Term Ortho-surgical Management of Temporomandibular Joint Ankylosis Secondary to Childhood Infection - Behnia, Hossein; Tehranchi, Azita; Behnia, Parsa; Tariverdi, Navid; Mesgarzadeh, Abolhassan (Galen Medical Journal, 2024)
This case report presents the management of a patient suffering from severe facial asymmetry and malocclusion. The patient was born in 2001 and was later hospitalized due to severe jaundice. At 5 years of age, the deviation in the jaws and the post condylectomy ankylosis of the TMJ and hip joint problems were evident. At age 7, a costochondral graft was performed. In the next phase, orthodontic treatment was started with hybrid functional therapy, but the treatment was unsuccessful due to the severity of the problem. At age 15, bilateral distraction osteogenesis was performed. The orthodontic plan for the maxilla was non-extraction. We expanded the upper arch and corrected the crossbite of the lateral incisors. Due to the difficulty of surgery, the impacted canine of the mandible remained impacted. The mandibular right lower incisor was removed due to severe crowding. Orthognathic surgery was performed after fixed orthodontic treatment.